Design of the PRINCESS trial: pre-hospital resuscitation intra-nasal cooling effectiveness survival study (PRINCESS) - Nordberg, Per; Taccone, Fabio Silvio; Castren, Maaret; Truhlár, Anatolij; Desruelles, Didier; Forsberg, Sune; Hollenberg, Jacob; Vincent, Jean-Louis; Svensoon, Leif (BMC emergency medicine, 2013)
BACKGROUND: Therapeutic hypothermia (TH, 32-34°C) has been shown to improve neurological outcome in comatose survivors of out-of-hospital cardiac arrest (OHCA) with ventricular tachycardia or fibrillation. Earlier initiation of TH may increase the beneficial effects. Experimental studies have suggested that starting TH during cardiopulmonary resuscitation (CPR) may further enhance its neuroprotective effects. The aim of this study was to evaluate whether intra-arrest TH (IATH), initiated in the field with trans nasal evaporative cooling (TNEC), would provide outcome benefits when compared to standard of care in patients being resuscitated from OHCA. METHODS/DESIGN: We describe the methodology of a multi-centre, randomized, controlled trial comparing IATH delivered through TNEC device (Rhinochill, Benechill Inc., San Diego, CA, USA) during CPR to standard treatment, including TH initiated after hospital admission. The primary outcome is neurological intact survival defined as cerebral performance category 1-2 at 90 days among those patients who are admitted to the hospital. Secondary outcomes include survival at 90 days, proportion of patients achieving a return to spontaneous circulation (ROSC), the proportion of patients admitted alive to the hospital and the proportion of patients achieving target temperature (<34°C) within the first 4 hours since CA. DISCUSSION: This ongoing trial will assess the impact of IATH with TNEC, which may be able to rapidly induce brain cooling and have fewer side effects than other methods, such as cold fluid infusion. If this intervention is found to improve neurological outcome, its early use in the pre-hospital setting will be considered as an early neuro-protective strategy in OHCA. TRIAL REGISTRATION: NCT01400373.
Keywords: výsledek terapie; urgentní zdravotnické služby; analýza přežití; Out-of-Hospital Cardiac Arrest; Fluorocarbons; neuroprotektivní látky; Hypothermia, Induced; Belgium; Emergency Medical Services; zástava srdce mimo nemocnici; Česká republika; Neuroprotective Agents; Survival Analysis; výzkumný projekt; Czech Republic; Treatment Outcome; terapeutická hypotermie; Administration, Intranasal; lidé; Research Design; Humans; fluorokarbony; Belgie; Sweden; aplikace intranazální; Švédsko